2017
DOI: 10.2525/ecb.55.113
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction Efficiency of Cadmium and Zinc by Arum (<i>Colocasia esculenta</i> L.) Grown in Hydroponics

Abstract: Cadmium (Cd) and Zinc (Zn) tolerance and phytoextraction efficiency of arum (Colocasia esculenta L.) were investigated in hydroponics. Plants were grown for 60 d in nutrient solution after addition of Cd and Zn at the levels of 0, 15, 30 and 60 mol L 1 and 0, 100, 500 and 1,000 mol L 1 , respectively. Growth of arum was unaffected by low levels of metal concentration (15 mol L 1 Cd and 100 mol L 1 Zn) whereas it decreased gradually with the increase of metal concentration in solution. Concentration of metals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The results showed that EDTA potentially reduced the phytotoxicity of heavy metal to Chinese mustard and also enhanced the cadmium accumulation. This finding also agreed well with the effects of Cd Zn Pb and Cr uptake with Arum (Colocasiaesculenta L.); Grass (Kochiascoparia) phytotoxicity and growth reported by Islam et al (2017) and Zhao et al (2015).…”
Section: Effects Of Pb and Edta On Esculentasupporting
confidence: 91%
“…The results showed that EDTA potentially reduced the phytotoxicity of heavy metal to Chinese mustard and also enhanced the cadmium accumulation. This finding also agreed well with the effects of Cd Zn Pb and Cr uptake with Arum (Colocasiaesculenta L.); Grass (Kochiascoparia) phytotoxicity and growth reported by Islam et al (2017) and Zhao et al (2015).…”
Section: Effects Of Pb and Edta On Esculentasupporting
confidence: 91%